2015
DOI: 10.1371/journal.pone.0126745
|View full text |Cite
|
Sign up to set email alerts
|

UV Light Reveals the Diversity of Jurassic Shell Colour Patterns: Examples from the Cordebugle Lagerstätte (Calvados, France)

Abstract: Viewed under UV light the diverse and exceptionally well-preserved molluscs from the Late Jurassic Cordebugle Konservat Lagerstätte (Calvados, Normandy, France) reveal fluorescent fossil shell colour patterns predating the oldest previously known instance of such patterns by 100 Myr. Evidently, residual colour patterns are observable in Mesozoic molluscs by application of this non-destructive method, provided the shells are not decalcified or recrystallized. Among 46 species which are assigned to twelve gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…It seems likely that only high concentrations of porphyrins result in visible pigmentation and this occurs most frequently in calcified structures. Porphyrin pigments in calcified structures are highly stable over time, with fluorescent patterns detectable in fossil shells as far back as the Jurassic [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that only high concentrations of porphyrins result in visible pigmentation and this occurs most frequently in calcified structures. Porphyrin pigments in calcified structures are highly stable over time, with fluorescent patterns detectable in fossil shells as far back as the Jurassic [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shell pigments identified using Raman have usually been determined to be modified carotenoids rather than melanins or tetrapyrroles, which might be explained by the fact that pigments are likely distributed across Mollusca in a phylogenetically relevant manner. [5,6,24,60,61] Most Raman studies have focused on bivalves, caenogastropods, or land snails, where pigments have rarely been identified chemically, but are unlikely to be tetrapyrroles, which tend to occur more frequently in Vetigastropoda (with some exceptions in Bivalvia and Caenogastropoda). Alternatively, signal from carotenoid-based pigments may be masking other shell pigments.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding how new biological colours have arisen is a fundamental challenge to our understanding of evolutionary ecology and developmental biology, but despite over a century of interest, the evolution of colour in molluscan shells is only just beginning to be explored in detail . Of particular interest is the observation that colour and the distribution of fluorescence associated with some pigmentation both seem to be distributed in a phylogenetically significant manner . Grant and Williams mapped the distribution of shell and periostracal colour onto a bivalve phylogeny and showed that the phylogenetic distribution of colour is statistically significant, as are the distributions of individual shell and periostracal colours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many invertebrate fossils also show preservation of colour and patterning visible to the naked eye (see Vinther, 2015: figs. 1D-H), and UV illumination and fluorescence microscopy, for example, can reveal preserved colouration patterns (note: not the original colours themselves) in gastropod shells (Caze et al, 2015). The actual extraction and chemical analysis of pig- ments from fossil specimens has demonstrated that pigments can be identified after millions of years and included in comparative analyses, using spectroscopy, chromatography, elemental analysis and chemical assays (Wolkenstein et al, 2008;Glass et al, 2012), and these same methods can be effectively deployed to invetigate colour in living taxa drawn from collections (Williams et al, 2016).…”
Section: Colour From the Pastmentioning
confidence: 99%